2012
DOI: 10.4236/fns.2012.31010
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacteria as Potential Functional Starter Cultures: A Case Study by MSc Students in Food Science and Technology (University of Foggia, Southern Italy)

Abstract: This research paper was the results of activity of MSc students of Food Science and Technology, attending the class “Biotechnology of Functional Starter”. Five strains of bifidobacteria (Bifidobacterium animalis subsp. lactis; B. longum subsp. infantis; B. breve; B. animalis subsp. animalis; B. bifidum) were evaluated in order to assess their suitability as functional starter cultures, by studying the following technological and probiotic traits: growth at different temperatures, NaCl amounts and pH values; ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
1
5
0
1
Order By: Relevance
“…Bifidobacterium crudilactis FR62/B/3 exhibited an optimal pH of growth of 5.0. This pH is lower than the optimum pH range (5.5 -7.0) described in the literature for the majority of bifidobacteria [2] [19] [20]. However, a similar optimum pH has been reported for B. animalis subsp.…”
Section: Discussionsupporting
confidence: 47%
“…Bifidobacterium crudilactis FR62/B/3 exhibited an optimal pH of growth of 5.0. This pH is lower than the optimum pH range (5.5 -7.0) described in the literature for the majority of bifidobacteria [2] [19] [20]. However, a similar optimum pH has been reported for B. animalis subsp.…”
Section: Discussionsupporting
confidence: 47%
“…lactis and B. longum subsp. infantis showed interesting probiotic traits (survival at pH 2.5 and with bile salts added) and promising technological properties (growth/survival under different conditions) (Bevilacqua and others ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that lactobacilli can also be useful for controlling autoimmune diseases such as inflammatory bowel disease (IBD), celiac disease, and type 1 diabetes [8,9]. Bifidobacterium is a pleomorphic rod, Gram-positive, non-spore forming, anaerobic, and used to be firstly named Bacillus Bifiduscommunis [10,11]. It has been shown that Bifidobacteria had different effects that promote health, that include the abstraction of procarcinogens, immunomodulation, banning of diarrhea and intestinal infections, and the synthesis of vitamins.…”
Section: Introductionmentioning
confidence: 99%